2010
DOI: 10.1177/15648265100311s105
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Fortification of Wheat Flour: Considerations and Current Recommendations

Abstract: Factors to guide a decision to fortify flour with vitamin A include the extent of deficiency, availability of other food vehicle options, the centrality of milling, market reach and population intake distributions of the flour products, the dietary vitamin A intake required, and associated costs. Large gaps persist in knowledge of these factors, which are needed to enable evidence-based fortification in most countries, leaving most decisions to fortify guided by assumptions. Where flour can and should be forti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…At the second Copenhagen Consensus in 2008, an expert panel of eight outstanding economists, including five Nobel laureates, ranked fortification with micronutrients (vitamins and minerals) among the top three international development priorities [15]. A new recommendation for fortification of wheat flour with vitamin A has been accepted [16]. Vegetable oil is, however, recognized as the most suitable vehicle for vitamin A fortification.…”
Section: Introductionmentioning
confidence: 99%
“…At the second Copenhagen Consensus in 2008, an expert panel of eight outstanding economists, including five Nobel laureates, ranked fortification with micronutrients (vitamins and minerals) among the top three international development priorities [15]. A new recommendation for fortification of wheat flour with vitamin A has been accepted [16]. Vegetable oil is, however, recognized as the most suitable vehicle for vitamin A fortification.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of vitamin A is affected by physical and chemical factors such as temperature, (water activity (aw) and moisture content), pH, oxygen, light, time, metallic ions, food composition and enzymes (Wirakartakusumah and Hariyadi, 1998;Manan, 1994). It has been reported that once premix is added at intended ratio concentrations to wheat flour, the stability of vitamin A continues to vary according to temperature, humidity, duration of storage, and other conditions of storage (Klemm et al, 2010). The instability might also be due to its chemical structure, having many double bonds susceptible to degradation (Wirakartakusumah and Hariyadi, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa, there is a proven indication of vitamin A source problems where there are two or three different sources using acetate instead of palmitate or using less stabilised forms which are cheaper (DOH/UNICEF, South Africa, 2009). Adjusting for 30 to 50% lost consideration during transportation, distribution, storage and processing of wheat flour and its products according to Klemm et al (2010), it implies that the minimum acceptable range for Nigerian vitamin A content for flour is 15,000 -21,000 IU/kg (4,504.5 -6,306.3 µgRE). Less than half (35.3%) of the flour samples met this range at 1month storage, 23.5% at 2 months storage and none at 3 months storage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations